Application of Azolla mycrophylla in combination with chicken manure to initiate rice organic farming in sandy soil. Issue 1 (July 2021) - Syamsiyah, J; Herawati, A; Mujiyo; Putri, E F; Pangastuti, T S; Afnani, L S; Putri, M W S
Abstract: Organic agriculture needs to be continuously developed, in anticipation of climate change and the availability of inorganic fertilizers Therefore, it is necessary to look for local various organic matter that is potential and affordable to farmers. This study aims to determine the effect of Azolla mycrophylla (AM) and chicken manure (CM) on the growth of rice cultivated organically in sandy soil. The pot research used a factorial completely randomized design with 2 factors, the first factor was 4 levels of Azolla mycrophylla, namely. 0, 50, 100, and 150 tonnes ha −1 . The second factor is chicken manure at a rate of 0, 20, and 40 tonnes ha −1 . Azolla mycrophylla and chicken manure were given 2 weeks before planting. The results showed that there was an interaction between AM and CM on plant height, number of leaves, and number of tillers. At the age of 84 days after planting, the highest plant height, leaf number, and a number of tillers were found in the treatment of AM 50 tonnes ha −1 and chicken manure 20 tonnes ha −1 . The use of Azolla mycrophylla 50 tonnes ha −1 is equivalent to reducing Urea fertilizer by 261 kg ha −1 or equivalent to N in the amount of 120 kg ha −1 .